COVID‐19 post hematopoietic cell transplant, a report of 11 cases from a single center. - Afadil Adam (Mediterranean Journal of Hematology and Infectious Diseases)
In late 2019 the coronavirus disease‐2019 (COVID‐19) pandemic caused by SARS Coronavirus 2 (SARS‐CoV‐2) started in Wuhan, China. Cancer patients are immunosuppressed from their disease and the therapy they receive.Hematopoietic cell transplant (HCT) recipients are a subgroup of patients that are severely immunocompromised and may be at an even higher risk of a complicated course during this infection.We herein report the outcomes and course of 11 sequential cases of HCT recipients infected by SARS‐CoV‐2 treated in our center.The patients age ranged from 17 to 60 years, the duration from transplant to infection ranged from day +5 to 192 months, 6 patients were post allo-HCT, 4 post auto-HCT and one had both allo and auto-HCT. The presenting symptoms were not different from other viral illnesses. The majority had mild COVID-19 stage, while 3 had moderate stage on presentation. None of the patients required oxygen supplementation nor mechanical ventilation.